## which translation rule can be used to prove that triangle r(10,6), s(8,4), t(6,6) and triangle r'(7,4), s'(5,2) t'(3,4)are congruent?

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

Answer:a) (x,y) → (x – 3, y – 2)

Step-by-step explanation:Comparing the pre-image points, r, s and t, to the image points, r’, s’ and t’, we see that the x-coordinates of the image are all 3 less than the x-coordinates of the image:

10-7 = 3; 8-5 = 3; 6-3 = 3

This means the first part of the translation rule will be x-3.

Now comparing the y-coordinates, we see that the y-coordinates of the image are all 2 less than the y-coordinates of the pre-image:

6-4 = 2; 4-2 = 2; 6-4 = 2

This means the second part of the translation rule will be y-2.

This gives us (x, y)→(x-3, y-2).

a) (x,y) =(x-3, y-2)